2002
DOI: 10.1038/labinvest.3780456
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Retinol-Binding Protein-1 Expression and Modulation during In Vivo and In Vitro Myofibroblastic Differentiation of Rat Hepatic Stellate Cells and Portal Fibroblasts

Abstract: SUMMARY:Cellular retinol-binding protein-1 (CRBP-1) is involved in vitamin A metabolism because it mediates both retinol esterification to retinyl esters and retinol oxidation to retinal and retinoic acid. CRBP-1 is highly expressed in the liver, particularly in hepatic stellate cells (HSC). In this study, we investigated the liver expression of CRBP-1 during experimental fibrogenesis. We also studied the regulation of CRBP-1 expression in cultured HSC and portal fibroblasts, two fibroblastic cell types involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
92
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 36 publications
11
92
0
2
Order By: Relevance
“…41 However, our findings differ from published reports that showed that PFs express CRBP-1 only after myofibroblastic differentiation. 7,16 We cannot explain this difference. Nonetheless, although PFs and HSCs in our study showed similar CRBP-1 profiles, PFs did not show the changes in PPAR-␥ expression seen in HSCs and failed to form lipid droplets in response to retinol treatment.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…41 However, our findings differ from published reports that showed that PFs express CRBP-1 only after myofibroblastic differentiation. 7,16 We cannot explain this difference. Nonetheless, although PFs and HSCs in our study showed similar CRBP-1 profiles, PFs did not show the changes in PPAR-␥ expression seen in HSCs and failed to form lipid droplets in response to retinol treatment.…”
Section: Discussionmentioning
confidence: 70%
“…10 These cells have been studied in culture, although generally after outgrowth from fragments of the biliary tree or late after isolation 16,17 ; the characteristics of PF myofibroblastic differentiation have not been studied. We suggest that myofibroblastic PFs are fibrogenic and that PFs in culture can be studied in much the same way as HSCs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Underlying mechanisms explaining HSC activation in aging revealed no modification in different proinflammatory mediators including TLR4, NFκB, and TGFβ (data not shown), but interestingly suggested alterations in retinoid metabolism and breakdown. In fact, aged livers exhibited down‐regulated CRBP‐1 together with over‐expressed PNPLA3, which have been associated with HSC activation and susceptibility to develop steatohepatitis (Bruschi et al, 2017; Uchio et al, 2002). …”
Section: Discussionmentioning
confidence: 99%
“…PFs are defined as a non‐HSC fibroblast population that can be found in the periportal mesenchyme surrounding the bile ducts; they are considered to be a heterogeneous population 11. However, studies on PFs have depended on isolation methods based on outgrowth from dissected bile segments,12 size selection,13 and purification of HSC marker‐negative, non‐HSC‐derived myofibroblasts by fluorescence‐activated cell sorting 14. None of these methods identify or isolate PFs by positive selection, thus hampering accurate evaluation of the cell population of interest.…”
Section: Introductionmentioning
confidence: 99%